Macro Mineral Status in Soil, Plant and Dairy Cattle in Andaman Group of Islands - Hegde, M. Sujata (Indian Journal of Animal Nutrition, 2018)
Present work was carried out in Prothrapur, Ferrargunj, Little Andaman, Diglipur, Rangat and Mayabunder blocks of the Andaman group of Island with the objective to estimate macro minerals status in soil, composite plant samples and dairy cattle. Samples of soil, composite plant and cattle blood serum each totalling 102 were taken randomly from all the six blocks. The samples were analysed for macro minerals (Ca, P, Mg, Na and K). The soil was deficient in Ca, P and Mg. The overall mean concentration of Mg (135.81±17.4 ppm) and P (9.42±0.59 ppm) in soil differed significantly (P<0.01) among the blocks whereas in plants the overall mean of P (2913.00±470.57 ppm) and Na (3330.76±323.36 ppm) differed significantly (P<0.01) among the blocks. The composite plant samples was found to be deficient in Mg and dairy cattle blood serum was found to be deficient in Ca, P and K across the blocks. Overall incidence (%) of deficiency in cattle blood serum was found to be 75.49, 33.33, 74.50, 100.00 and 15.69% in Ca, Mg, P, K and Na, respectively. The incidence of deficiency of Ca, P and K in cattle blood serum was found to be above 70% in Diglipur and Rangat blocks. In cattle blood serum, Ca (6.83±0.530 mg/dL), Mg (1.82±0.110 mg/dL), P (2.90±0.380 mg/dL) and Na (519.58±54.940 mg/dL) differed significantly (P<0.01) among the six blocks. Significant (P<0.01; P<0.05) positive correlation was obtained between soil and plant for Ca, Na, K and between plant and cattle for Mg whereas such correlation was obtained between soil and cattle only for Ca.